Dampak Sistem Shift Kerja dan Beban Kerja terhadap Keseimbangan Kehidupan Kerja (Work-Life Balance) Perawat di Rumah Sakit Pratama Tapan - Hafiza, Maisya Afmi; Zusmawati, Zusmawati (Lembaga Yasin AlSys, 2026)
Although work-life balance has become an important issue in human resource management, studies that specifically discuss the effect of shift work systems and workload on nurses’ work-life balance in regional hospitals remain limited. This study aims to analyze the effect of the shift work system and workload on nurses’ work-life balance at Pratama Tapan Hospital. This study used a quantitative approach with a survey design, involving 59 nurses selected through total sampling. Data were collected using a questionnaire and analyzed using multiple linear regression. The results show that the shift work system has a positive and significant effect on work-life balance. Workload also has a positive and significant effect on work-life balance. This finding contributes to the development of human resource management studies, particularly regarding employee well-being in health institutions. The conclusion of this study emphasizes that a well-regulated shift work system and controlled workload are important factors in improving nurses’ work-life balance. The practical implications of this study indicate the need to improve work scheduling systems and distribute workload more evenly as a hospital management strategy to support nurses’ work-life balance.